Nigerian drug index : based on the essential drugs list - Atueyi, Ifeanyi (Lagos : Pharmanews, 1991)
This is a revised edition with the introduction of the Essential Drugs List (EDL). It also contains an index of manufacturers and agents. The index is prepared with doctors, pharmacists and allied professionals in mind, and is intended to serve as a reference book on drugs currently marketed in Nigeria.
Includes index
usc 10/11/2021
Ref.
Keywords: Drug incidences; Drug records; Nigeria